SISTEM PENDUKUNG KEPUTUSAN UNTUK PEMILIHAN PENERIMA BANTUAN REHABILITASI RUMAH DENGAN METODE MOORA (Studi kasus: Desa Simpang Peut, Kecamatan Seunuddon, Kabupaten Aceh Utara, Aceh ): DECISION SUPPORT SYSTEM FOR RECIPIENT SELECTION HOUSE REHABILITATION ASSISTANCE WITH THE MOORA METHOD - Sayed Fachrurrazi; Veri Ilhadi; Amna Yusra (LPPM Universitas Abdurrab, 2026)
Home rehabilitation is a government program that aims to improve the condition of the houses of the poor or underprivileged so that they are habitable again. A habitable house is not only seen from the physical aspect of the building, but also from the aspects of security, comfort, health, and the feasibility of functioning as a place to live. The distribution of home rehabilitation assistance in Simpang Peut Village, Seunuddon District, North Aceh Regency, faces obstacles in determining the most suitable recipient objectively and measurable. Out of 25 candidate recipients, only 3 can be selected, so a fair and transparent selection method is required. This research aims to build a Decision Support System (SPK) based on the MOORA (Multi-Objective Optimization on the Basis of Ratio Analysis) method. This system uses 10 assessment criteria, namely land ownership status, house ownership status, roof condition, wall condition, floor condition, socio-economic status, income, employment, number of dependents, and the type of assistance needed. The MOORA method is applied to produce an automatic ranking based on the weight of the specified criteria. The results of the ranking are validated through verification with the village apparatus and compared with the previous manual selection results, thus ensuring the suitability of the system results with the field conditions. The research results showed that Wahyudin obtained the highest score of 0,024849, followed by Rakiyah and Mansur Taleb as recipients of assistance.